PENERAPAN STRATEGI PEMBELAJARAN MENGGUNAKAN APLIKASI EDUCAPLAY DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS X SMK NEGERI 4 GOWA - Sri Ayu Lestari (Jurnal Education, 2025)
The aim of this research is to increase students' interest in learning by using the interactive media Educaplay during the learning process. This PTK includes planning, implementation, observation and reflection. The research subjects were 27 students of class X TKJ 2 SMK Negeri 4 Gowa. Student learning outcomes are still low, only 33.3% of students meet the criteria, with an average score of 73.70. After implementing educaplay interactive media. Cycle I showed an increase in the average student score to 79.62 and the level of learning completion increased to 40.7%. However, in cycle I the set indicators had not been achieved, so it was continued to cycle II, where the percentage of students who met the criteria was 81.4%. The results of classroom action research in class